Improving Badminton Service Learning Outcomes Through Learning Media for Class IX Middle School Students - Edi Sahputra (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The general objective of this research is to improve students' outcomes through the implementation of Badminton Learning using Learning Media. Additionally, this research is conducted to gain in-depth information about the application of Badminton Learning using Learning Media. The research design employed is Action Research. The subjects in this study are 28 students from the Eighth grade at SMP Negeri 9 Langsa. The research consists of two meetings spanning two cycles. Each cycle comprises three sessions. The first cycle indicates that through action, students can self-motivate. From this first cycle, the result is 26%, indicating it is not yet completed. In the second cycle, as a reflection of the first cycle, it also shows that actions improve student learning outcomes. The result of the second cycle is 89%, indicating completion. Based on the findings of this research, it can be concluded that: (1) Badminton Learning using Learning Media enhances students' learning outcomes, (2) Badminton Learning using Learning Media motivates students and engages them actively in the learning process.